SASIMI (Aquaponic System in A Circular Economy) Model with 5R Principles to address environmental pollution - Lustina Fajar Prastiwi; Rani Destia Wahyuningsih; Syahrul Naufal Firmansyah; Fitria Nada; Erika Puji Nurwahidiyah; Ariq Syauqi Billah; Mila Maulidya Anwar (University of Merdeka Malang, 2024)
The Tanusi Farmers Group in Sumberejo Village, Batu District, faced significant challenges in waste management and limited agricultural land, which hindered their ability to adopt sustainable farming practices. To address these issues, the SASIMI (Aquaponic System in Circular Economy) initiative was implemented. The system aimed to reduce waste by applying the 5R principles. It repurposed inorganic waste, such as plastic, as planting media in aquaponics and utilized maggots as biological agents to process organic waste into compost. The methodology of SASIMI included several stages, such as preparation, education on waste management and maggot cultivation, aquaponic system preparation, training on implementation and maintenance, sustainability training, and evaluation. The implementation of SASIMI yielded significant results. Maggot cultivation was able to establish 10 cultivation sites that process up to 20 kilograms of organic waste per month, converting it into compost. Additionally, 10 aquaponics systems were established, reducing 15 kilograms of plastic waste by repurposing it as planting media. Economically, the circular economy approach contributed to reducing household expenses. The aquaponics systems provided a sustainable source of fresh produce, leading to a 22 percent reduction in monthly expenditures on vegetables for participating households.